Kae1 of Saccharomyces cerevisiae KEOPS complex possesses ADP/GDP nucleotidase activity. Issue 23 (9th December 2022) - Li, Qian-Xi; Liu, Jia-Cheng; He, Ming-Hong; Zhou, Jin-Qiu
Abstract : The KEOPS complex is an evolutionarily conserved protein complex in all three domains of life (Bacteria, Archaea, and Eukarya). In budding yeast Saccharomyces cerevisiae, the KEOPS complex ( Sc KEOPS) consists of five subunits, which are Kae1, Bud32, Cgi121, Pcc1, and Gon7. The KEOPS complex is an ATPase and is required for tRNA N6-threonylcarbamoyladenosine modification, telomere length maintenance, and efficient DNA repair. Here, recombinant Sc KEOPS full complex and Kae1–Pcc1–Gon7 and Bud32–Cgi121 subcomplexes were purified and their biochemical activities were examined. KEOPS was observed to have ATPase and GTPase activities, which are predominantly attributed to the Bud32 subunit, as catalytically dead Bud32, but not catalytically dead Kae1, largely eliminated the ATPase/GTPase activity of KEOPS. In addition, KEOPS could hydrolyze ADP to adenosine or GDP to guanosine, and produce PPi, indicating that KEOPS is an ADP/GDP nucleotidase. Further mutagenesis characterization of Bud32 and Kae1 subunits revealed that Kae1, but not Bud32, is responsible for the ADP/GDP nucleotidase activity. In addition, the Kae1 V309D mutant exhibited decreased ADP/GDP nucleotidase activity in vitro and shortened telomeres in vivo, but showed only a limited defect in t 6 A modification, suggesting that the ADP/GDP nucleotidase activity of KEOPS contributes to telomere length regulation.